A case study on hazardous grounds: Stabilized legacy waste and occupational health concerns at the Okhla landfill, New Delhi - Sonam Angmo; Shachi Shah (Environment Conservation Journal)
This study evaluates the status of stabilized legacy waste and the impact of work and environmental conditions on the health of landfill workers at Okhla landfill, New Delhi. A mixed- methods strategy was utilized to collect primary and secondary data, including a cross- sectional questionnaire distributed to 107 landfill workers. Approximately 55-60 lakh tons of legacy waste are present at the site, an around 06 Trommels with bio-mining and bioremediation efforts underway to clear the site by 2024.The survey findings indicated that 5% of workers believed that approximately 400-500 trucks deposit waste in the landfill daily, whereas 95% were unaware of this fact. The study unveiled that a significant proportion of participants experienced occupational health hazards intermittently, including skin allergies (36.17%), respiratory illnesses (31.91%), eye redness/hair loss (23.40%), and cardiac problems (8.51%). 51% of workers reported poor rest room conditions and lack of leachate collection and treatment facilities were identified as major concerns. Workers demonstrated a good understanding of leachate generation and its seasonal variability. Adequate Personal Protective Equipment (PPEs) and regular health checkups for workers. Improved hygiene in workers' restrooms. Consequently, it emphasized the imperative for adequate Personal Protective Equipment (PPEs), regular health checkups, improved hygiene in workers' restrooms, and the implementation of leachate collection facilities in the study area.